Adjusting the molecular clock: The importance of circadian rhythms in the development of glioblastomas and its intervention as a therapeutic strategy - Wagner, Paula Micaela (2021)
Gliomas are solid tumors of the central nervous system (CNS) that originated from differentglial cells. The World Health Organization (WHO) classifies these tumors into four groups (I-IV)with increasing malignancy. Glioblastoma (GBM) is the most common and aggressive type of braintumor classified as grade IV. GBMs are resistant to conventional therapies with poor prognosis after diagnosis even when the Stupp protocol that combines surgery and radiochemotherapy is applied.Nowadays, few novel therapeutic strategies have been used to improve GBM treatment, lookingfor higher efficiency and lower side effects, but with relatively modest results. The circadian timingsystem temporally organizes the physiology and behavior of most organisms and daily regulatesseveral cellular processes in organs, tissues, and even in individual cells, including tumor cells. Thepotentiality of the function of the circadian clock on cancer cells modulation as a new target for novel treatments with a chronobiological basis offers a different challenge that needs to be considered in further detail. The present review will discuss state of the art regarding GBM biology, the role of the circadian clock in tumor progression, and new chrono-chemotherapeutic strategies applied for GBM treatment.